Generativna umetna inteligenca v izobraževanju: Analiza stanja v primarnem, sekundarnem in terciarnem izobraževanju - Licardo, Marta; Kranjec, Eva; Lipovec, Alenka; Dolenc, Kosta; Arcet, Barbara; Flogie, Andrej; Plavčak, Darja; Ivanuš Grmek, Milena; Bednjički Rošer, Barbara; Sraka Petek, Barbara; Laure, Maruša (University of Maribor Press, 2025)
Generative Artificial Intelligence in Education: An Analysis of the State in Primary, Secondary, and Tertiary Education. The monograph presents the first comprehensive and systematic analysis of the use of generative artificial intelligence (GEN-AI) in education in Slovenia. The research, structured through eleven thematic areas, covers various stakeholders in the education system at primary, secondary, and tertiary levels. The content offers an in-depth insight into the types, frequency, and purposes of GEN-AI use in primary and secondary schools, as well as universities. It addresses the challenges faced by stakeholders in using GEN-AI, ethical issues, and the pedagogical opportunities provided by GEN-AI tools. The analysis also includes the need for training, perceived technical limitations, and suggestions for optimising the use of GEN-AI in teaching processes. Special attention is given to the perception of the impact of GEN-AI on various aspects of educational work, including organisational support, perceived benefits, user experience, and the experience of learning, teaching, and leadership processes when using GEN-AI. The monograph represents an important scientific and professional contribution to the field of educational sciences and offers valuable guidance for shaping strategic policies and decisions in the field of education and upbringing in the future.